Evaluation of aesthetics of indigenous architectural structures in metropolitan Kumasi from pre-colonial era to the present - Asamoah, Margaret Adwoah (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of the Degree of Master of Arts in Art Education.